2021
DOI: 10.1155/2021/7143815
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness Computer-Assisted Language Teaching by Big Data Analysis

Abstract: This paper presents an in-depth study and evaluation analysis of the effects of the computer-assisted language teaching method on foreign language learning through its application. Using an empirical research approach, a practical study of computer-assisted English language teaching was conducted to verify the effects of CALL on oral language learning. In exploring the effects of CALL on students’ oral learning, including the effects on fluency, accuracy, and complexity of oral expressions, as well as the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This method aims to merge big data technology with foreign language teachers' education concepts and teaching ability analysis. Wang et al (2021) presented an in-depth study and evaluation analysis of the effects of computer-assisted language teaching (CALL) on foreign language learning. Their empirical research focuses on the practical study of CALL in English language teaching, specifically assessing its effects on oral language learning.…”
Section: Related Workmentioning
confidence: 99%
“…This method aims to merge big data technology with foreign language teachers' education concepts and teaching ability analysis. Wang et al (2021) presented an in-depth study and evaluation analysis of the effects of computer-assisted language teaching (CALL) on foreign language learning. Their empirical research focuses on the practical study of CALL in English language teaching, specifically assessing its effects on oral language learning.…”
Section: Related Workmentioning
confidence: 99%
“…Studies have shown that CALL can improve language proficiency, vocabulary acquisition, and reading comprehension among language learners (Alam & Mizan, 2019;Enayati & Gilakjani, 2020;McNeil, 2016). However, the effectiveness of CALL may depend on the quality of the software and its compatibility with the learners' needs and preferences (Wang et al, 2021).…”
Section: Computer-assisted Language Learning (Call)mentioning
confidence: 99%
“…Wang, H. et al analyzed the role of computer-assisted teaching in English language teaching by using empirical research to analyze the impact on students' speaking ability through computer-assisted. From the results, computer-assisted teaching can enhance students' interest in learning English and increase their confidence in expressing themselves orally in English [12]. Bao, W. et al set up an English learning website to enhance students' motivation to learn English and provide an environment for students to learn independently, which is They analyzed the application of technology by English teachers in the process of English teaching based on the TPACK framework, which provided practical guidance for the reform of the English teaching process [14].…”
Section: Introductionmentioning
confidence: 99%